Pelatihan Penggunaan Google Classroom dan Google Meet bagi Tenaga Pendidik SMP di Kabupaten Sumba Timur - Erwin Randjawali; Mayun Erawati Nggaba; Anggriati Ledu Ngaba; Yuliana Tamu Ina Nuhamara; Elsy S H Taunu; Darius Imanuel Wadu; Stevvileny Angu Bima; Iona Lisa Ndakularak; Yuliana S Eko; Mega Retno Wulandari; Itha Priyastity; Irna Natalis Sanit (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The implementation of this Community Service activity is motivated by the problems experienced by partners at SMP Kristen Payeti. The teachers in that school have not been able to take advantage of online learning applications such as Google Classroom and Google Meet. Therefore, to overcome the partner's problems, training was carried out by the PkM Team of Program Studi Pendidikan Matematika Universitas Kristen Wira Wacana Sumba, which aims to educate the teachers so that they can increase their knowledge and skills related to the use of the two applications. The training activities were carried out using lectures, demonstrations, and simulations using Google Classroom and Google Meet. While the stages of implementation include the preparation of training modules, preparation of training rooms, and implementation of training. The results of this service activity indicate that there is an increase in the knowledge and skills of teachers as trainees in using the two applications. Thus it can be concluded that the purpose of this service activity has been achieved. The follow-up carried out was to monitor the use of these two applications by teachers in the implementation of online learning.